The truth about immigration : why successful societies welcome newcomers - Hernandez, Zeke (St. Martin's Press, 2024)
"The go-to book on immigration: fact-based, comprehensive, and nonpartisan. Immigration is one of the most controversial topics in the United States and everywhere else. Pundits, politicians, and the public usually depict immigrants as either villains or victims. The villain narrative is that immigrants pose a threat--to our economy because they steal our jobs; our way of life because they change our culture; and to our safety and laws because of their criminality. The victim argument tells us that immigrants are needy outsiders--the poor, huddled masses whom we must help at our own cost if necessary. But the data clearly debunks both narratives. From jobs, investment, and innovation to cultural vitality and national security, more immigration has an overwhelmingly positive impact on everything that makes a society successful. In The Truth About Immigration, Wharton professor Zeke Hernandez draws from nearly 20 years of research to answer all the big questions about immigration. He combines moving personal stories with rigorous research to offer an accessible, apolitical, and evidence-based look at how newcomers affect our local communities and our nation. You'll learn about the overlooked impact of immigrants on investment and job creation; realize how much we take for granted the novel technologies, products, and businesses newcomers create; get the facts straight about perennial concerns like jobs, crime, and undocumented immigrants; and gain new perspectives on misunderstood issues such as the border, taxes, and assimilation. Most books making a case for immigration tell you that immigration is good for immigrants. This book is all about how newcomers benefit you, your community, and your country. Skeptics fear that newcomers compete economically with locals because of their similarities and fail to socially assimilate because of their differences. You'll see that it's exactly the opposite: newcomers bring enduring economic benefits because of their differences and contribute positively to society because of their similarities. Destined to become the go-to book on one of the most important issues of our time, this book turns fear into hope by proving a simple truth: immigrants are essential for economically prosperous and socially vibrant nations"--